METHODS OF MEDICAL REHABILITATION OF THOSE WHO HAVE SUFFERED COMPLICATIONS OF COVID-19 - Butabaev , Makhmudjon; Minavarov , Rasul; Utanov , Zafar; Isakov , Kobiljon; Kamalova , Nigora (Medical science of Uzbekistan, 2023)
The Covid-19 pandemic could reach several million people worldwide. Presumably, 5-15% of them will need medical rehabilitation after suffering from pneumonia and acute respiratory distress syndrome. The goals of medical rehabilitation at the preclinical stage are to achieve the correction of diseases that contribute to the development of Covid-19 complications (acute respiratory distress syndrome, from 15% to 33 %; acute respiratory failure, 8 %; acute heart failure, from 7% to 20 %; secondary infection, from 6% to 10 %; acute renal failure, from 14% to 53 %; septic shock, from 4% to 8 %; cardiomyopathy, in 33% of critical; disseminated intravascular coagulation, in 71 % of the dead; pregnancy complications are not excluded. Rare complications include mucormycosis and encephalitis. Encephalitis occurs only in about 0.215% of hospitalized patients, but among patients with severe disease, its frequency increases to 6.7%). Non-medicinal technologies have a number of advantages over medicines that have a side effect, and such as glucocorticoids and antibiotics lead to a deterioration in the prognosis of the underlying disease. Medical rehabilitation in the intensive care unit is aimed at reducing the risks of complications and increasing the functional reserves of the body, as well as reducing the area and degree of lung damage, preventing extrapulmonary complications, including secondary infection. The main goal of medical rehabilitation in a hospital setting is to reduce the severity of symptoms, resorption and repair in the lesion of lung tissue, reduce the development of fibrosis, provide bronchial drainage for prevention of secondary infection. In addition, the timely transfer of the patient to a specialized stage of medical rehabilitation makes it possible to increase the functional reserve of the respiratory muscles and exercise tolerance. The second specialized stage of medical rehabilitation can be carried out in the conditions of a sanatorium-resort organization. The goals of this stage are not only to reduce symptoms and increase tolerance to physical activity, but also to improve the quality of life, psychological rehabilitation, and restoration of working capacity.